Influence of temperature and sugar addition on soymilk fermentation by probiotic bacteria - Silvija Brletić; Rajka Božanić; Sandy Lovković (Mljekarstvo)
Fermented soymilk beverages were produced by fermentation withmonocultures of probiotic bacteria: Bifidobacterium lactis Bb12, Lactobacillus acidophilus La5 and Lactobacillus casei Lc01 (Chr. Hansen’s, Denmark), at two different temperatures (37 °C and 43 °C), with and without 5 % sugar addition (sucrose for Bb12 and La5, and glucose for Lc01). pHvalues and numbers of viable cells were measured throughout the fermentation. For all tested probiotic bacteria temperature 37 °C was more appropriated than 43 °C. The fermentation process in the case of all three monocultures were shortened by an addition of sugars and viable counts at the end of the fermentation were increased. The influence of sugar on acid production and viable cells count was greatest in soymilk fermented with monoculture L. casei Lc-01. The choice of monoculture did not have a significant influence on the appearance and consistency of the fermented soymilk, apart when the achieved acidity was not enough and soymilk did not coagulate, like in the case of fermentation with strain Lc-01 without glucose addition.